2018
DOI: 10.1039/c8fo01095a
|View full text |Cite
|
Sign up to set email alerts
|

Downregulating PI3K/Akt/NF-κB signaling with allicin for ameliorating the progression of osteoarthritis:in vitroandvivostudies

Abstract: Osteoarthritis (OA) is characterized by the degeneration and destruction of articular cartilage. Allicin, a dietary garlic active constituent, exerts anti-inflammatory effects on several diseases. However, its effects on OA have not been clearly elucidated. In this study, we explored the effects of allicin on OA in both in vitro and in vivo models. Allicin inhibited interleukin-1β (IL-1β) induced overproduction of nitric oxide, inducible nitric oxide synthase, prostaglandin E2, and cyclooxygenase-2, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…The allicin treatment decreased both proinflammatory cytokines and these effects were exerted at the systemic and tissue levels. In vitro and in vivo allicin modulates the production of IL-1β, IL-6 and TNF-α at both the mRNA and protein levels [ 24 , 25 , 26 ]. Other studies described that allicin has anti-inflammatory effects [ 27 ] and suppresses both oxidative stress and proinflammatory cytokines [IL-1, TNF-α and Monocyte Chemoattractant Protein-1 (MCP-1)] [ 26 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The allicin treatment decreased both proinflammatory cytokines and these effects were exerted at the systemic and tissue levels. In vitro and in vivo allicin modulates the production of IL-1β, IL-6 and TNF-α at both the mRNA and protein levels [ 24 , 25 , 26 ]. Other studies described that allicin has anti-inflammatory effects [ 27 ] and suppresses both oxidative stress and proinflammatory cytokines [IL-1, TNF-α and Monocyte Chemoattractant Protein-1 (MCP-1)] [ 26 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, allicin reduces the activation of NFκβ, the nuclear translocation and the phosphorylation of Iκβ induced by IL-1 [ 25 ]. Moreover, allicin suppresses IL-1β-induced phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) phosphorylation, a pathway involved in the regulation of NFκβ [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, inhibition of PI3K/AKT/mammalian target of rapamycin pathway could induce articular chondrocyte autophagy and suppress inflammatory processes in OA rats [14]. Allicin alleviates the progression of OA by inactivating the PI3K/AKT/NF-jB pathway [15]. Blocking PI3K/AKT signaling can reduce post-traumatic OA or tumor necrosis factor-a-induced OA [16,17].…”
mentioning
confidence: 99%
“…Similarly, Arellano Buendia et al (2018) had revealed that the allicin treatment decrease proinflammatory cytokines ( il-1 β and il-6 ) showing the same effect on both systemic and tissue levels of diabetic rats. Moreover, both in vitro and in vivo , allicin has been reported to modulate the production of il-1 β, il-6 and tnfα at both the mRNA and protein levels ( Alam et al, 2018 ; Qian et al, 2018 ). Therefore, these results suggested that allicin supplementation could enhance immunity and alleviate inflammation of large yellow croaker larvae.…”
Section: Discussionmentioning
confidence: 99%